2015
DOI: 10.4238/2015.september.8.9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic hypoxia on penile erectile function in rats

Abstract: ABSTRACT. We examined the relationship between chronic hypoxia and erectile dysfunction in rat and its possible pathogenic mechanism. Forty-eight white male adult Sprague-Dawley rats were randomly divided into a test group and a control group. In accordance with the experimental time (2, 6, and 10 weeks), each group was divided into 3 subgroups, with 8 rats in each subgroup. Rats in the test group were fed in an airtight hypoxia cabin, while rats in the control group were maintained in a normal environment, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
8
0
2
Order By: Relevance
“…There is currently no evidence concerning the possible long-term impairment of lung function following SARS-CoV-2 infection; however, considering the scale of the current pandemic and the similarities between SARS-CoV and SARS-CoV-2 [84], there is sufficient reason to suspect a high rate of fibrotic lung function abnormalities in COVID-19 survivors. In such patients, the impaired oxygen saturation could impair erectile function; some evidence in support comes from animal models [85,86] as well as from clinical reports [87,88]. From a pathophysiological standpoint, this is hardly surprising, as oxygen is one of the substrates required for the synthesis of nitric oxide (NO) by the enzyme NO synthase, whose activity is severely blunted in hypoxia [87].…”
Section: Pulmonary Fibrosis and The Effects Of Hypoxiamentioning
confidence: 99%
“…There is currently no evidence concerning the possible long-term impairment of lung function following SARS-CoV-2 infection; however, considering the scale of the current pandemic and the similarities between SARS-CoV and SARS-CoV-2 [84], there is sufficient reason to suspect a high rate of fibrotic lung function abnormalities in COVID-19 survivors. In such patients, the impaired oxygen saturation could impair erectile function; some evidence in support comes from animal models [85,86] as well as from clinical reports [87,88]. From a pathophysiological standpoint, this is hardly surprising, as oxygen is one of the substrates required for the synthesis of nitric oxide (NO) by the enzyme NO synthase, whose activity is severely blunted in hypoxia [87].…”
Section: Pulmonary Fibrosis and The Effects Of Hypoxiamentioning
confidence: 99%
“…As age advances, the gonadal steroid hormones and testosterone decrease, nerve conduction slows, the efficiency of the vascular microcirculation of the penis is reduced, and the smooth muscle/collagen ratio in the copora cavernosum decreases [28]. Yu et al [29] demonstrated that chronic hypoxia might cause ED due to the decrease in the quantity of nNOS nerve fibers and expression on eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic intermittent hypoxia (CIH) is one of the most important and direct consequences of obstructive sleep apnea (OSA) [8,9] with studies showing a higher ED incidence in male patients with chronic hypoxia [10]. Hypoxia may affect erectile function, neuronal nitric oxide synthase (nNOS) and endothelial nitric oxide synthase (eNOS) expression leading to erectile dysfunction under hypoxic conditions in murine models [11,12]. Constitutively expressed nNOS and eNOS isoforms mediate penile erection by producing nitric oxide (NO), which has been recognized as playing a major role in the physiology of penile erection [1,2].…”
Section: Introductionmentioning
confidence: 99%